Motivational Behaviour of Lecturers in English Department at Halu Oleo University: Student's Perception - Dana, Agung; Jaya, Amir; Nurnia, Nurnia (Journal of Teaching English, 2019)
Motivation is the reason of someone's behaviour. It explains peoples' needs, action, and desires. Motivation can also be defined as a   peoples' reason to change his/her behaviour. In language classes, lecturers have been trying a lot of things to motivate their student in a class. There have been the number of studies in the educational field to prove that lecturer or teacher has an important role in student’s motivation. In that matter, this study aimed to identify motivating lecturer’s behaviour in language class according to students. Participant of the study included 90 students which consist of 40 students for pilot study and 50 students as the main study, and those students were all from the English Study Program at Halu Oleo University. The data were collected using the questionnaire that administrated to these participants, and 10 students were also interviewed to get in-depth information on lecturer motivational behaviour. The qualitative data were analysed through descriptive statistic. The result presented some significant insight on lecturer's motivational behaviour that would serve lecturers as a guide for classroom implications.